Volumetric & Transport Behavior of Neutral Amino Acids in Different Concentrations of an Electrolyte at 25°C - Dhir, Vaneet; Grewal, R. P. Singh (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
Apparent molar volumes, V2, ? of glycine, DL-?-alanine, DL-?-amino-n-butyric acid, L-valine and L-leucine in water and in (0.25, 0.5, 0.75, 1.0, 1.5, 2.0) mol?kg-1 aqueous potassium nitrate solutions have been determined at T= 298.15 K from density measurements. The standard partial molar volumes at infinite dilution, V20 obtained from V2, ? , have been used to calculate the corresponding volumes of transfer, ?tV0 from water to aqueous potassium nitrate solutions. The hydration number, nH, side chain contributions and volumetric interaction coefficients of these amino acids have also been calculated. The ?tV0 values for the studied amino acids are positive, and these values increase with an increase in the concentration of NaNO3 .